PENGEMBANGAN PROSES ENZIMATIS GELOMBANG MIKRO UNTUK PRODUKSI ASAM LEMAK DARI BUAH SAWIT SECARA IN SITU - Yulianto, Mohammad Endy; Abidin, Zainal; S, FS Nugraheni; Paramita, Vita (METANA, 2010)
Abstract Vegetable oil is one of plantation commodity and used as food source and oleochemical. One of the connection between vegetable industry and oleochemical industry is the conversion of vegetable oil into fatty acid. Indonesia is one of major producer of Crude Palm Oil (CPO), Palm Kernel Oil (PKO) and Cocos Nucifera Oil (CNO), but Indonesia is also import fatty acid in the application of paint, plastics, cosmetics, detergent and soap industry. These facts show a pityfull condition of vegetable oil industry. Therefore, it is neccesary to take an effort in order to fulfill our domestic demand of fatty acid. Up to now, the fatty acid is produce by converting CPO into fatty acid, which provide high cost production due to the expensive process of CPO production. An alternative process was proposed by cutting the two stages of fatty acid production into one stage. This stage covered the direct enzymatics production of fatty acid from fresh fruit of palm oil. The lipase of palm oil is inactivated in a microwave based-enzymatics hydrolysis bioeractor. The research objectives was developing the fatty acid production through microwave biochemical process by activate the lipase enzyme of the fresh fruit of palm oil. The parameters examined were including pH, ratio of water-fruit, and the milling of the palm oil as time function. The lipase activity as a result of microwave tunning up process was increasing along with the increasing of the reaction temperature. Without the addition of buffer, the acidity of the system decreased along with the production of fatty acid. Along with the increasing of the water concentration, the fatty acid produced was also increased. Â  Key Words: fatty acid, lipase, microwave